Efecto de la GnRh en protocolos de sincronización sobre la fertilidad de novillas Bos taurus indicus (2023)
Hormonal treatments that combine the use of Gonadotropin Releasing Hormone (GnRH) and Prostaglandin F2α (PGF2α) have been able to synchronize estrus and ovulation in dairy cows and buffaloes, but in heifers the results have been very variable, reporting dispersion in estrus, persistence of follicles and low ovulation rates1. Therefore, in order to reduce the variability of these results, protocols have been created in combination with progesterone release devices; in this regard, the P4-Cosynch treatment that combines the use of Progesterone (P4) with GnRH and PGF2α, which has given good results in the synchronization of cows and heifers of dairy and beef breeds, stands out. According to ASOCEBÚ data, 95% of the Colombian cattle population is zebu or has zebu genetics. Therefore, this study could contribute to the dynamization of productive processes and to the increase of the breeding stock. Considering the above, the objective of this study was to evaluate the effect of GnRH hormone in fixed-term artificial insemination protocols on the fertility of Bos taurus indicus heifers. For the study, 158 clinically healthy Brahman cyclic and acyclic heifers with a body condition score of four were synchronized. The experimental treatments corresponded to six protocols that included the following hormones GnRH-PGF2-GnRH (T1 and T2), DIBGnRH-PGF2-GnRH (T3 and T4) and DIB-GnRH-PGF2-eCG-GnRH (T5 and T6). The animals were assessed for preovulatory follicle size by ultrasonography using an ALOKA Co., Ltd. UST-5820-5 equipped with a 5MHz linear translator, the screen was split in 2B mode, the image was frozen with the Freeze option, and the variables were analyzed by Chi-square test of independence and comparison of proportions between two populations. With the synchronization protocols, a total pregnancy rate of 10.7% (T1), 16.6% (T2) 36.8% (T3) 41.9% (T4) 38.7% (T5) and 27.68% (T6) was obtained. The effect (P= 0.0803) between treatments was found when comparing pregnancy proportions, it was found that T1 and T2 were statistically equal (p>0.05). The same happened with treatments T3, T4, T5 and T6, but differences (p≤0.05) were found between treatments T1 and T2 when compared with treatments T3, T4, T5 and T6. On the other hand, there were no differences (P ≥ 0.05), in the average preovulatory follicle size being these 10.28; 11.21 and 11.77 mm for heifers synchronized with treatments 1-2, 3-4 and 5-6, respectively. The use of GnRH hormone in combination with progesterone in Cosynch protocol significantly improves pregnancy rates in Bos indicus heifers, compared to the traditional Cosynch protocol.